Respiratory insufficiency related to copd accelerates systemic inflammation, under-nutrition, and angiogenesis in esophageal malignancies - Krzystek-Korpacka, M.; Matusiewicz, M.; Diakowska, D.; Grabowski, K.; Neubauer, K.; Kustrzeba-Wojcicka, I.; Terlecki, G.; Gamian, A. (Experimental Oncology, 2008)
A number of esophageal cancer patients suffer from respiratory insufficiency due to the coexistence of chronic obstructive pulmonary disease (COPD). Aim: To test the hypothesis that COPD-related systemic hypoxemia may result in accelerated inflammation, malnutrition, and angiogenesis in esophageal cancer patients. Methods: Serum levels of C-reactive protein (CRP), albumin, transferrin, interleukin-1, interleukin-6, interleukin-8, TNF- a, platelet-derived growth factor (PDGF-BB), and midkine and patient BMI and weight-loss rate were determined and compared with blood oxygenation status (pO2, SaO2) in 35 esophageal cancer patients and 42 controls. Results: The incidence of cachexia tended to be higher in patients with systemic hypoxemia (67% vs 40%, p = 0.169). Mean SaO2 level was also significantly decreased in cachectic patients (90.3 vs 93.3%, p = 0.026) and pO2 exhibited a similar trend (58.0 vs 63.4 mmHg, p = 0.120). Transferrin (234 vs 316 mg/dl, p = 0.005) and albumin (31.9 vs 37.1 mg/dl, p = 0.002) concentrations were reduced and CRP was elevated (129.9 vs 54.7 mg/l, p = 0.004) in hypoxemic patients and correlated with pO2 (r = 0.47, p = 0.016; r = 0.48, p = 0.012; r = –0.37, p = 0.064) and SaO2 (r = 0.52, p = 0.006; r = 0.53, p = 0.006; r = –0.40, p = 0.042). Interleukin-6 (9.97 vs 2.21 pg/ml, p = 0.005) and midkine (2101 vs 944 pg/ml, p < 0.001) were elevated and PDGF-BB was decreased (12.2 vs 17.3 pg x 10-6/PLT, p = 0.014) in hypoxemic compared with normoxemic patients. Interleukin-6 and midkine negatively correlated with pO2 (r = –0.44, p = 0.016; r = –0.42, p = 0.011) and SaO2 (r = –0.54, p = 0.003; r = –0.57, p < 0.0001) and PDGF-BB correlated positively (r = 0.53, p = 0.003; r = 0.44, p = 0.020). Interleukin-8 level was affected by pO2 (r = -0.55, p = 0.015) and SaO2 (r = –0.55, p = 0.018) only in hypoxemic patients. Conclusions: COPD-related systemic hypoxemia negatively affects the status of esophageal cancer patients by accelerating inflammation, under-nutrition, and angiogenesis. Многие больные раком пищевода страдают от респираторной недостаточности из-за развития хронического обструктивного легочного заболевания (COPD). Цель: Проверить гипотезу о возможной связи системной гипоксемии, ассоциированной с COPD, с усилением воспалительных процессов, истощением и ангиогенезом у больных раком пищевода. Методы: у 35 больных раком пищевода и 42 здоровых доноров определяли уровень CRP, альбумина, трансферина, интерлейкина-1, интерлейкина-6, интерлейкина-8, TNF-α, PDGF-BB и мидкина в сыворотке крови, показатели BMI и потери веса больных, а также показатели уровня оксигенации крови (pO2 , SaO2 ). Результаты: частота возникновения кахексии была выше у больных с системной гипоксемией (67 против 40%, p = 0,169). Средний уровень SaO2 был также значительно снижен у больных с кахексией (90,3 против 93,3%, p = 0,026), с той же тенденцией и для уровня pO2 (58,0 против 63,4 mmHg, p = 0,120). Концентрации трансферина (234 против 316 мг/дл, p = 0,005) и альбумина (31,9 против 37,1 мг/дл, p = 0,002) были снижены, CRP повышен (129,9 против 54,7 мг/л, p = 0,004) у гипоксемических пациентов, что кореллировало с показателями pO2 (r = 0,47, p = 0,016; r = 0,48, p = 0,012; r = –0,37, p = 0,064) и SaO2 (r = 0,52, p = 0,006; r = 0,53, p = 0,006; r = –0,40, p = 0,042). Уровень интерлейкина-6 (9,97 против 2,21 pg/ml, p = 0,005) и мидкина (2101 против 944 pg/ml, p < 0,001) был также повышен, а уровень PDGF-BB понижен (12,2 против 17,3 pg × 10-6/PLT, p = 0,014) у гипоксемических больных по сравнению с показателями при нормоксемии. Уровни интерлейкина-6 и мидкина негативно кореллировали с показателями pO2 (r = –0,44, p = 0,016; r = –0,42, p = 0,011) и SaO2 (r = –0,54, p = 0,003; r = –0,57, p < 0,0001) и позитивно — с PDGF-BB (r = 0,53, p = 0,003; r = 0,44, p = 0,020). На уровень интерлейкина-8 влияли pO2 (r = –0,55, p = 0,015) и SaO2 (r = –0,55, p = 0,018) только у больных с гипоксемией. Выводы: ассоциированная с COPD системная гипоксемия негативно влияет на состояние больных раком пищевода за счет ускорения воспалительных процессов, истощения и ангиогенеза